Successful transcatheter embolization of splenic artery pseudoaneurysm in acute necrotising pancreatitis. - Mohamad, Nasibah; Sulaiman, Fatin Syahirah; Ehsan, Norhafizah; Hussin, Izazul (The Interventionalist Journal, 2021)
Splenic artery pseudoaneurysm is a rare condition commonly arises as a sequelae of pancreatitis. Pseudoaneurysm is clinically silent until it ruptures. Thus, untreated pseudoaneurysm carries a high mortality rate up to 90%. We present a case of necrotising pancreatitis complicated with unruptured splenic artery pseudoaneurysm, which was found incidentally from computed tomography (CT) of abdomen. Patient was presented with symptomatic anemia and bleeding from the abdominal drain. We proceeded with embolization of pseudoaneurysm by using Histoacryl glue, resulting in successful complete resolution of pseudoaneurysm with good patient outcome. Transcatheter embolization is considered the current treatment of choice for pseudoaneurysm as it provides an alternative to conventional surgery due to its high successful rate. In this case report, we want to shed light on an alternative treatment approach of the splenic artery pseudoaneurysm.